EKSISTENSI PENGGUNA FINSTAGRAM SEBAGAI BENTUK KEBEBASAN REMAJA BEREKSPRESI (STUDI ANALISIS ETNOGRAFI VIRTUAL) - Marisda; Nurliah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
The development of the civilization of the times, the increase in technology and the internet in the world of life has also expanded by showing its existence not only in the real world but also in the virtual world. This has led to various efforts made as a form of channeling people's existence in actualizing themselves on various platforms on social media, one of which is Instagram. Social media users are then managed with different purposes so that a phenomenon that still occurs today is Finstagram or the management of two Instagram accounts by a user with the aim of managing the image and impression on the general public on the main account, and showing freedom of expression without being burdened by the image on the second accountbased on the concept of dramathurgy theory. The purpose of this research is to find out the motivation and factors of finstagram so that it can be a channel for freedom of expression. The type of research used is descriptive qualitative, with data collection techniques carried out by distributing questionnaires and interviews to be analyzed using cyber media analysis techniques with micro and macro levels based on virtual ethnographic analysis studies. The results of the study found that informants in utilizing the finstagram phenomenon to maintain the image and impression they manage but still channel their free expression without being burdened by the image they manage on the main account by managing two accounts with significant goals, and based on the experience of researchers as ethnographers, finstagram has functionality, namely interpretation, linkage, transmission of value, entertainment, information, and manipulate to persuade. They are with efforts and efforts to maintain their existence through various ways in the real world and the virtual world.